Proceedings of the DESIGN 2018 15th International Design Conference 2018
DOI: 10.21278/idc.2018.0537
|View full text |Cite
|
Sign up to set email alerts
|

Design Automation State of Practice - Potential and Opportunities

Abstract: Design Automation has been in focus of research and application for several decades. This paper aims at establishing the current view of design automation and identification of potential for adoption based on a survey conducted in German speaking countries and a hypothesis based multivariate analysis based on networks. The findings show that design automation is still considered a means of automation of repetitive design tasks and potential for enhanced application exists. The necessity for methods supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 13 publications
0
17
2
Order By: Relevance
“…On the other hand, the generation of several solutions using the optimization was highly appreciated among the participants, as it supports ideation of problem solving. This is contrary to the answers given to the acceptance and usage assessment from a general perspective, where engineers were still most interested in automating repetitive tasks, and also contrary to the results of the study in Rigger and Vosgien (2018), where obtaining alternative solutions was ranked as a minor driver for implementing DA. This discrepancy can be explained by the fact that only regarding the former part the engineers have seen an approach for finding several solutions before answering the questions.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the generation of several solutions using the optimization was highly appreciated among the participants, as it supports ideation of problem solving. This is contrary to the answers given to the acceptance and usage assessment from a general perspective, where engineers were still most interested in automating repetitive tasks, and also contrary to the results of the study in Rigger and Vosgien (2018), where obtaining alternative solutions was ranked as a minor driver for implementing DA. This discrepancy can be explained by the fact that only regarding the former part the engineers have seen an approach for finding several solutions before answering the questions.…”
Section: Discussioncontrasting
confidence: 87%
“…(III) By comparing as-is and to-be processes and by using quantitative and/or qualitative assessments, the potential and expected benefits of DA solution are elaborated. For the quantitative assessment, metrics, such as lead-time reduction, can be derived from a list of DA drivers defined in Rigger and Vosgien (2018). Similarly, qualitative evaluation with end-users, e.g.…”
Section: Approachmentioning
confidence: 99%
“…Given the fact that designers are knowledgeable about design automation opportunities for the early phase, they also see the potential for design automation application as indicated by the metrics rating. This is contradictory to previous findings of survey that showed that designers do not consider design automation relevant for the early stages of the design process (Rigger and Vosgien, 2018). Most likely, this is linked to the lack of knowledge about the opportunities.…”
Section: Implications and Future Workcontrasting
confidence: 87%
“…Current practice for potential estimation of design automation, which accounts for the assessment of the impact of design automation on design performance, relies on qualitative estimation of the value of design automation based on high-level design automation drivers. These drivers account for motivational aspects for design automation implementation in practice (Amen et al, 1999;Cederfeldt et al, 2005;Rigger and Vosgien, 2018) and most often, only estimations of potential time savings for repetitive tasks in product development are reported, e.g. Frank et al (2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation